Reformas al codigo organico integral penal regularizando las competencias automovilisticas en el Ecuador - Silva Zambrano, Luis Fernando (2015)
"REFORMS TO THE CODE ORGANIC COMPREHENSIVE CRIMINAL REGULATING COMPETENCES AUTOMOBILE IN ECUADOR" Ecuador, a country owner of a wonderful landscape and with a large number of amateur Motorsports, since it is sufficient to observe in the rallies organized by different organizations, the number of spectators and fans, but unfortunately in recent times have been many obstacles to be able to move forward with this sport that is a little dangerous and costly, but I wonder what sport doesn't have risks?, take the case of soccer, has been observed in the different media that many athletes have died from different circumstances in the same sports field, but we must take into account that as well is the order of life. Many sports have all securities case and sometimes by any circumstances happens some kind of accident, but we are not going to set aside a sport, Since you say: If young people are engaged in the sport will leave aside the drugs and alcohol, so you want that Motorsports are regulated, and thus are not carried out in clandestine races that are dangerous for the participants and for the citizens in general, since it is not possible that the State simultaneously authorize a car race and Moreover you repress an offence or sanction as civil wrongful actsIf an accident within this sport happens. Have existed many drawbacks with regard to car contests, since it is very difficult and not impossible that national transit agency gives the authorization to perform a competition, since they argue that necessary for the accomplishment of the same guarantees there is no, is why that desire, the power regulation concerning car contestsWe educate people in related to the poor or little information that we have about the requirements, the conditions of vehicles, their obligations the organizers, sponsors, pilots, fans and citizens in general. Why are requested to regulate concerning car contests, it should give an example of what happened in a car competition held in the city of Ambato, where unfortunately a police motorcycle, entering via where competition was carried out without observing that it was not ending and a race car that was at high speed, since it was within a competition, noticing the presence of the uniformed tries to stop but by the speed of the vehicle manages to only try to dodge the motorcycle, but the clashes by the back and motorcycle loses control and falls the motorized apparatus; It is rather amazing that the vehicle and the driver of the racing car were arrested, without so far since it is treated as an offence common and not as an accident happened in a sporting event, for this and many more reasons is requested that regulate concerning car contests and things like these cease to happen can be solvednow that people who invest time and money in preparing their vehicles and several times have had to pay damages to third parties by the recklessness of the people. There are clubs of pilots in each province of the Ecuador either rally, climb mountain, piques, 4 x 4 and the Grand Tour to the Republic of Ecuador, which is the competition that all pilots want to participate to the places of our beautiful Ecuador, then if there are so many clubs that support the sport, because not only sponsor a sport as it is the case of football that often has bonded people for disputes between the equipment; However car contests does not happen to this, since many participants with the unique slogan to achieve a podium and achieve his long-desired glass, since not so much competing for prizes economic, since many times there are, but it is the satisfaction of compete, get the adrenaline within to strive with several automotive and arrive in the first stalls, that if counting with all securities that must have a vehicle such as: rollbar, seat belts, fire extinguishers, etc, and the pilots using the equipment needed to be able to protect your life. Then if we try as far as possible have higher securities with approved very expensive equipment, but as we know it is for our safety, therefore we ask that more than regulate you can access and import equipment for vehicles and drivers free of tariffs, putting limits on imports because we know they exist everywhere, unscrupulous people who want to take advantage of the situation and want to import a whole store for your benefit and that is not so, you want to be an exclusive benefit for pilots; This is why that clubs, will be in charge of verifying that there are no anomalies in this sense and the pilots are the only beneficiaries and with them would increase the number of people who engage in this sport so exciting.